Information Frictions among Firms and Households - Sebastian Link; Andreas Peichl; Christopher Roth; Johannes Wohlfart (ZBW - Leibniz Information Centre for Economics, 2021)
We use surveys of German households and firms to study the extent of information frictions among different groups of economic agents. Firms' expectations about the central bank policy rate, inflation, and aggregate unemployment are more aligned with expert forecasts and less dispersed than households'. Moreover, firms update their policy rate expectations significantly less when provided with an expert forecast and do not extrapolate to expected own borrowing rates, while households extrapolate to personal rates. Our results challenge previous findings that information frictions among firms are as large as those among households, which has important implications for modeling heterogeneity in macroeconomic expectation formation.
Keywords: D83; D84; E71; 330; Information frictions; firms; households; expectation formation; interest rates